2023
DOI: 10.2147/hiv.s311613
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Regimens and Care Models for Older Patients Living with HIV: Are We Doing Enough?

Abstract: With improved access to antiretroviral therapy throughout the world, people are aging with HIV, and a large portion of the global population of people with HIV (PWH) is now age 50 or older. Older PWH experience more comorbidities, aging-related syndromes, mental health challenges, and difficulties accessing fundamental needs than the population of older adults without HIV. As a result, ensuring that older PWH are receiving comprehensive healthcare can often be overwhelming for both PWH and the providers. Altho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 115 publications
0
5
0
Order By: Relevance
“…In Nigeria, one of the most common causes of patient non-compliance is the presence of drug side effects (66.7%), no transportation costs to the hospital, traveling, forgetting, and avoiding being seen by other people [63,64]. This is different from studies in Tanzania, Uganda, and Zambia, which found that 29% of patients had missed taking medication, and stavudine drugs caused more symptoms felt by patients [65]. The cause of non-adherence due to side effects of this drug also occurred in a study conducted in Nigeria, namely 66.7% [66].…”
Section: Discusionmentioning
confidence: 75%
“…In Nigeria, one of the most common causes of patient non-compliance is the presence of drug side effects (66.7%), no transportation costs to the hospital, traveling, forgetting, and avoiding being seen by other people [63,64]. This is different from studies in Tanzania, Uganda, and Zambia, which found that 29% of patients had missed taking medication, and stavudine drugs caused more symptoms felt by patients [65]. The cause of non-adherence due to side effects of this drug also occurred in a study conducted in Nigeria, namely 66.7% [66].…”
Section: Discusionmentioning
confidence: 75%
“…Perceptions of increased vulnerability to frailty and infection among people living with HIV add another layer of concern about aging. HIV stigma and the association of NCD treatment regimens with antiretrovirals can lead to hesitancy in seeking medical treatment and in adhering to prescribed regimens (e.g., anti-hypertensive medications) [ 29 ]. Limited job options add to the financial strain of managing chronic conditions and suggest age-related discrimination in the workplace in addition to older people taking on the assumption that they are not capable of performing work [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Zambian Ministry of Health promotes family and social support due to loss of functional and earning capacity, and supports networks for people living with chronic conditions [ 30 ]. However, intersectional stigma requires intersectional discrimination laws and multisectoral policies that recognize the different dimensions of aging in their full context to make transformative changes [ 29 , 31 ]. For instance, older people may experience unemployment, job loss or lower wages as a result of multiple social identities, such as “living with a chronic condition,” “disabled,” and “poor.” Discrimination laws will need to ensure that these aspects along with, for example, gender, sexuality, and age, are treated synergistically.…”
Section: Discussionmentioning
confidence: 99%
“…Estos modelos enfatizan la importancia de incluir durante la consulta aspectos que van más allá del manejo del VIH, para integrar otros componentes de salud como el contexto social, la medicina preventiva, los síndromes geriátricos y la salud mental, entre otros. 7,37,38 Este estudio tiene algunas limitaciones, entre ellas su índole retrospectiva y que los datos proceden de una sola institución. Sin embargo, el Instituto Nacional de Cancerología es uno de los pocos centros de cáncer de referencia en la Ciudad de México que atiende a población sin seguro médico proveniente de diversos estados del país, por lo que su población es una buena representación de las personas que viven con VIH y cáncer.…”
Section: Discussionunclassified